EFEKTIVITAS KOMUNIKASI PEMASARAN ONLINE (VIA TWITTER) TERHADAP PENINGKATAN PELANGGAN LUMINOS RENTAL STUDIO FOTO - Nurnawati Hindra, Zidni Haula & (Transformasi, 2015)
This study was descriptive-qualitative in nature, in which Luminos was a creative company,one service of which is Photograph Study Rental, the service starting to be operated since2012. And only in 2012 did this service find an appropriate marketing communication„formula‟ and could it increase its income volume and customer number. The onlinemarketing communication using twitter social media well had affected the income andcustomer number of Luminos photograph studio rental since 2012 until today. Theachievement of measurable and effective marketing communication then became the basis forLuminos to promote its product to the customers. It was said as effective and measurableconsidering the increased income of Photograph Studio Rental from October 2012 until todayin which such the increase affected the number of customers coming to Luminos, most ofwhich were college (university) students. In addition, the positive effect of marketing throughits twitter was the increased number of followers for @luminoskreatif account from 600 to1200 followers.Key Words: Marketing Communication Effectiveness, Luminos, Twitter, Increased Customers